18F-FDG-PET correlates of aging and disease course in ALS as revealed by distinct PVC approaches. (2022) - Ferraro, Pilar M.; Campi, Cristina; Miceli, Alberto; Rolla-Bigliani, Claudia; Bauckneht, Matteo; Gualco, Lorenzo; Piana, Michele; Marini, Cecilia; Castellan, Lucio; Morbelli, Silvia; Caponnetto, Claudia; Sambuceti, Gianmario; et al.
Abstract: Purpose: The partial volume effect (PVE) complicates PET studies of neurodegenerative diseases, since a decreased 18 F-FDG retention might be influenced by atrophy-related changes of cortical regions. Multiple partial volume correction (PVC) methods have been therefore developed, but their application in amyotrophic lateral sclerosis (ALS) is still rare. Additionally, even if metabolic changes have been established in ALS, no study yet has investigated how these may be influenced by aging and disease course. The aim of the present study was therefore to apply and compare multiple PVC approaches to explore aging and disease course-related hypometabolism in ALS. Methods: PET and MRI data from 15 ALS patients were analyzed using PETSurfer to implement 4 distinct PVC methods: noPVC, Meltzer (MZ), Müller-Gärtner (MG) and Symmetric Geometric Transfer Matrix (SGTM). For each method and Region of Interest (ROI), the 18 F-FDG value was regressed against subject age and disease duration. Results: MG/SGTM application almost halved the number of regions showing a significant age-related hypometabolism, while the same effect was not observed for disease course, where only the distribution of identified regions varied. Three distinct patterns emerged: regions showing a significant age/disease course-related effect across all the different methods, regions yielding significance only with MG/SGTM application, and regions maintaining significance only with noPVC/MZ application. Conclusions: Significant changes in the distribution of aging and disease course-related hypometabolism were observed when the effect of the underlying structural status was considered, supporting the need for investigate the impact of PVE on PET-assessed metabolic changes in clinical and research settings. Graphical Abstract: ga1 Highlights: 4 PVC methods were compared to evaluate aging and disease course-related hypometabolism in ALS. 3 patterns of significance emerged across ROIs: with all PVC methods, only with MG/SGTM, and only with noPVC/MZ. The PVE exerts a significant impact on the detection of metabolism alterations distribution.